An investigation on tensile and fatigue properties of cast Al-7Si-1.5Cu alloy applied in cylinder head considering size effect phenomenon. (June 2022) - Zhao, Cheng-zhang; Huang, Wei-qing; Liu, Jin-xiang; Ren, Pei-rong; Zuo, Zheng-xing; Yan, Kang-jie
Abstract: The cylinder head is one of the most critical diesel engine components. Under service conditions, different loads are exerted on the cylinder head, leading to the failure of various degrees at different positions of the cylinder head. In this study, the differences in mechanical properties at the different positions of the cylinder head are investigated by sampling specimens, metallography measurement, tensile and fatigue tests, and fracture surface analysis. Meanwhile, the Weibull statistical distribution method is used to analyze the size effect of the specimen. The results show that the microstructure features of the cylinder head exhibit high spatial heterogeneity. The mechanical properties are affected by microstructure features. The tensile properties of the top plate are optimum, followed by the flame plate, and the connecting wall has the worst properties. The difference in tensile properties at different positions is mainly affected by the grain and eutectic structure. In the same position, the tensile and fatigue properties of standard specimens are better than small specimens. The porosity is the critical parameter determining the tensile and fatigue properties of the different specimens. In addition, based on the statistical analysis of mechanical properties, the relationship of mechanical properties between the standard and small specimens was established. Through the established relationship, the mechanical properties of small specimens can be used to predict the mechanical properties of standard specimens, and the predicted value is in good agreement with the experimental data. Graphical Abstract: ga1 Highlights: Standard and small specimens were cut from the cylinder head. The microstructure with high heterogeneity of the cylinder head was observed. The mechanical properties variation caused by microstructure was investigated. The mechanical properties relationship of the different specimens was established. The mechanical properties of standard specimens were predicted by the relationship.